Nilai-nilai Aswaja di Maddin Jaryul ‘Ulum Kecamatan Kuwarasan - Irawan, Riya; Irodati, Fibriyan (IAINU Kebumen, 2022)
This article was written to provide an overview of the cultivation of aswaja values in learning at madrasah diniyah Jaryul 'Ulum, Kuwarasan District. To obtain data on the cultivation of aswaja values, the author conducts interview, observation and documentation techniques. Madrasah Diniyah is a non-formal educational institution whose existence is very effective in increasing the religious knowledge of its students, which is not obtained in formal schools. The learning objectives at Madrasah Diniyah are not only on technical knowledge and skills (hard skills), but also on the skills of managing themselves and others (soft skills). Therefore, it is important to instill aswaja values in madrasah diniyah educational institutions, a process that involves instilling knowledge, love and instilling good behavior that becomes a pattern/habit. The values of aswaja that are considered good and very important are internalized into every jiw